Konsep dan Implementasi Moderasi Beragama dalam Hukum Positif di Indonesia - Haniyah, Haniyah (Proceedings of Annual Conference for Muslim Scholars, 2022)
The Indonesian nation has the motto bhineka tunggal ika, different but still one, a country that has religious diversity, ethnicity, skin color, and language. With the uniqueness and specialty of the Indonesian nation as plural and sovereign nation, the value of the unity of the Republic of Indonesia, must be instilled in every citizen. To maintain harmonization against existing differences, especially religious differences, it must be planted with moderate attitudes. As a country with a Muslim-majority population, tolerance must be forward so that there is no action that leads to the division of the nation. With the expectation of cases of violence that in the name of religion must immediately get attention and the concept of religious moderation is expected to be the right solution. Moderation of Beragama does not make weak in religion and the practice of religion, because religious moderation remains guided by the Qur'an and hadith, as well as recognized schools. in Indonesia. As a legal country, Indonesia has an obligation to maintain the unity of the Republic of Indonesia (NKRI) state, through positive law in Indonesia. In religious moderation, believers should not extremely practice religious teachings but must always find common ground. One of the principles of religious moderation is to find common ground by embracing and protecting extreme groups, happiness, and positive laws in the world. Indonesia adopts the principle of moderation through the concept of deradicalization because basically terrorism originated from radicalization, so the deradicalization program is an effort to fight terrorism effectively. As stipulated in law No. 5 of 2018 on combating terrorism crimes, to neutralize radical understanding through the concept of deradicalization.